ANALISA SISTEM OPERASI DAN DAYA PRODUKSI PEMBANGKIT LISTRIK TENAGA AIR KAPASITAS 7,5 MW DI PLTA PARAKAN KONDANG - Selamet Nurjaman, Ade; Susandi, Dony (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
One of the energy needs that may be almost inseparable in human life at this time is the need for electrical energy. as is known to obtain electrical energy through a long and complicated process, but given the nature of this electrical energy that is easily channeled and easy to convert into other forms of energy such as light energy, heat energy, chemical energy, mechanical energy, sound, images , etc. Electric energy utilization has been widely used for household, commercial, government, industrial and so on. Indonesia Power UBP Saguling Parakan Kondang Hydroelectric Power Plant (PLTA) is one of the power plants that is able to meet the electricity needs of Java-Bali with the source of generation coming from water. To meet the electricity needs of Java - Bali, each plant will try to minimize errors in each production process. One of them is by analyzing the operating system and production power at each plant so that the targeted production power can be achieved, as well as the Parakan Kondang Hydroelectric Power Plant. Parakan Kondang Hydroelectric Power Plant (PLTA) always implements "Daily Meeting", this is done for the planning of the plant's operating system in order to achieve the targeted production targets. In addition, the Parakan Kondang Hydroelectric Power Plant (PLTA) also does every job according to the Standard Operating Procedures (SOP) so that no accidents occur in each of its work. And the results of operating system planning will be discussed at the next "Daily Meeting", to find out what problems occur during operation at the Parakan Kondang Hydroelectric Power Plant.